Antibiofilm Formation Activity of Terminalia bellerica Plant Extract Against Clinical Isolates of Streptococcus mutans and Streptococcus sobrinus Implication in Oral Hygiene - Yadav, Shivani (International Journal of Pharmaceutical & Biological Archive, 2012)
Antibiofilm Formation Activity of Terminalia bellerica Plant Extract Against Clinical Isolates of Streptococcus mutans and Streptococcus sobrinus Implication in Oral Hygiene